Pengaruh Ukuran Perusahaan, Leverage, Dan Profitabilitas Terhadap Manajemen Laba Pada Perusahaan Kosmetik - Hasbullah, Hasbullah; Lusika, Lindri (CV. ULIL ALBAB CORP, 2024)
This study aims to determine the effect of Firm Size (total Assets), Leverage (DAR), and Profitability (ROA) on EarningsManagement in cosmetic companies listed on the IDX for the 2016-2022 period. This research is a quantitative research with an associative approach using secondary data. The research population totaled 7 years of financial reports and 35 research samples were obtained using the purposive sampling method according to certain criteria and the data used were financial report data for 7 years from 2016-2022. The analysis technique used is the classical assumption test, multiple linear regression test and hypothesis testing. The model was tested using SPSS version 20. The results of this study indicate that partially firm size has a negative effect on earnings management, both leverage (DAR) partially has a positive effect on earnings management, thirdly, profitability has a positive effect on earnings management. management. The four company measurements, leverage (DAR), and profitability (ROA) simultaneously affect earnings management.